The antifibrotic adipose-derived stromal cell: Grafted fat enriched with CD74+ adipose-derived stromal cells reduces chronic radiation-induced skin fibrosis. (20th June 2020) - Borrelli, Mimi R.; Patel, Ronak A.; Adem, Sandeep; Diaz Deleon, Nestor M.; Shen, Abra H.; Sokol, Jan; Yen, Sara; Chang, Erin Y.; Nazerali, Rahim; Nguyen, Dung; Momeni, Arash; Wang, Kevin C.; et al.
Abstract: Fat grafting can reduce radiation-induced fibrosis. Improved outcomes are found when fat grafts are enriched with adipose-derived stromal cells (ASCs), implicating ASCs as key drivers of soft tissue regeneration. We have identified a subpopulation of ASCs positive for CD74 with enhanced antifibrotic effects. Compared to CD74− and unsorted (US) ASCs, CD74+ ASCs have increased expression of hepatocyte growth factor, fibroblast growth factor 2, and transforming growth factor β3 (TGF-β3) and decreased levels of TGF-β1. Dermal fibroblasts incubated with conditioned media from CD74+ ASCs produced less collagen upon stimulation, compared to fibroblasts incubated with media from CD74− or US ASCs. Upon transplantation, fat grafts enriched with CD74+ ASCs reduced the stiffness, dermal thickness, and collagen content of overlying skin, and decreased the relative proportions of more fibrotic dermal fibroblasts. Improvements in several extracellular matrix components were also appreciated on immunofluorescent staining. Together these findings indicate CD74+ ASCs have antifibrotic qualities and may play an important role in future strategies to address fibrotic remodeling following radiation-induced fibrosis. : Abstract : CD74⩲ adipose-derived stromal cells express multiple growth factors with antifibrotic activity. These cells decrease production of collagen type 1 by TGF-B1 stimulated fibroblasts, and when used to enrich fat grafts, they promote remodeling of radiation-induced fibrosis in the overlying skin.CD74⩲ adipose-derived stromal cells express multiple growth factors with antifibrotic activity. These cells decrease production of collagen type 1 by TGF-B1 stimulated fibroblasts, and when used to enrich fat grafts, they promote remodeling of radiation-induced fibrosis in the overlying skin.